2022
DOI: 10.3389/fphar.2022.940572
|View full text |Cite|
|
Sign up to set email alerts
|

A Review on the Antidiabetic Properties of Moringa oleifera Extracts: Focusing on Oxidative Stress and Inflammation as Main Therapeutic Targets

Abstract: Moringa oleifera is one of the popular plants that have shown significant health benefits. Certainly, preclinical evidence (predominantly from animal models) summarized in the current review supports the beneficial effects of Moringa oleifera leaf extracts in combating the prominent characteristic features of diabetes mellitus. This includes effective control of blood glucose or insulin levels, enhancement of insulin tissue sensitivity, improvement of blood lipid profiles, and protecting against organ damage u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 149 publications
(196 reference statements)
1
18
0
Order By: Relevance
“…The dose of M. oleifera extract (0.3 g/kg/day) and the treatment period (2 weeks) used in the present study have been previously shown to be safe and effective [11,12] . The use of a 70 % ethanolic extract is supported by previous research, indicating its strong antioxidant activity [13–15] …”
Section: Resultssupporting
confidence: 73%
“…The dose of M. oleifera extract (0.3 g/kg/day) and the treatment period (2 weeks) used in the present study have been previously shown to be safe and effective [11,12] . The use of a 70 % ethanolic extract is supported by previous research, indicating its strong antioxidant activity [13–15] …”
Section: Resultssupporting
confidence: 73%
“…Popularly called ‘the miracle tree’, M. oleifera , or moringa, is the most nutrient dense tree known 6 . It is highly nutritional and packed full of iron, vitamins C, A, D, B, E, carotene, a host of essential and fatty oils, beta‐carotene, potassium, fats and proteins, phenols, flavonoids, alkaloids, glucosinolates, terpenes, and so forth, 7 Because of these so many constituents, M. oleifera has been examined for its biological usefulness as an immune booster, a concentration enhancer, an anti‐cardiovascular disease agent, an antioxidant, an antiviral, an antimicrobial agent, an antiulcer agent, an antiasthma agent, an anti‐atherosclerotic agent, an anti‐diabetic agent, an anti‐obesity agent, a hepato‐protective agent, a wound‐healing aid, an aphrodisiac, a nephroprotective agent, in dental remineralization, in bone health, in scurvy, in Crohn's disease, and more 8 . There is even a claim that the plant has been used to treat 300 different illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is highly nutritional and packed full of iron, vitamins C, A, D, B, E, carotene, a host of essential and fatty oils, beta-carotene, potassium, fats and proteins, phenols, flavonoids, alkaloids, glucosinolates, terpenes, and so forth, 7 Because of these so many constituents, M. oleifera has been examined for its biological usefulness as an immune booster, a concentration enhancer, an anti-cardiovascular disease agent, an antioxidant, an antiviral, an antimicrobial agent, an antiulcer agent, an antiasthma agent, an anti-atherosclerotic agent, an anti-diabetic agent, an anti-obesity agent, a hepato-protective agent, a wound-healing aid, an aphrodisiac, a nephroprotective agent, in dental remineralization, in bone health, in scurvy, in Crohn's disease, and more. 8 There is even a claim that the plant has been used to treat 300 different illnesses. The extract from the leaves of M. oleifera was also found to regulate the status and levels of thyroid and cholesterol respectively in rats, 6 and these extracts have been found to contain glycine, alanine, leucine, valine, aspartic acid, histidine, glutamic acid, threonine, isoleucine, lysine, methionine, phenylalanine, tryptophan, and cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the insufficient production of insulin by the pancreas or the ineffective degradation of the insulin produced (WHO, 2023). One of the pathophysiological mechanisms involved in the progression of diabetes is oxidative stress with the unbalanced generation of reactive oxygen species such as hydroxyl radical and superoxide anion and reduced activity of antioxidant mechanisms such as catalase, glutathione peroxidase, and superoxide dismutase (Mthiyane et al, 2022). Since ancient times and nowadays, natural products (plant, fungal, animal, microbial, or mineral) are being increasingly used compared to therapeutic alternatives due to the presence of active compounds with pharmacological properties (Cortes-Gallardo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%